Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1007/s00787-013-0416-8
|View full text |Cite
|
Sign up to set email alerts
|

Emotion recognition in girls with conduct problems

Abstract: A deficit in emotion recognition has been suggested to underlie conduct problems. Although several studies have been conducted on this topic so far, most concentrated on male participants. The aim of the current study was to compare recognition of morphed emotional faces in girls with conduct problems (CP) with elevated or low callous-unemotional (CU+ vs. CU-) traits and a matched healthy developing control group (CG). Sixteen girls with CP-CU+, 16 girls with CP-CU- and 32 controls (mean age: 13.23 years, SD=2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(54 citation statements)
references
References 37 publications
4
41
0
Order By: Relevance
“…8,9 These studies have established that women with CD have a higher deficit of facial acknowledgement of happiness, sadness, and fear -emotions linked to empathic answers and prosocial behavior. Research has also described that these adolescents present slower emotional processing, which limits the decoding of such emotions and generates a delay in the empathic responses needed to understand and affectively bond with the emotional and mental states of others.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 These studies have established that women with CD have a higher deficit of facial acknowledgement of happiness, sadness, and fear -emotions linked to empathic answers and prosocial behavior. Research has also described that these adolescents present slower emotional processing, which limits the decoding of such emotions and generates a delay in the empathic responses needed to understand and affectively bond with the emotional and mental states of others.…”
Section: Introductionmentioning
confidence: 99%
“…Another report from Northern Europe, based on a Finnish register-based regional study, hints that the use of firearms plays a major role in explaining the northern excess in young Finnish male suicide rates [9]. In a German clinical sample, the relationship of callous-unemotional traits with conduct problems in girls has been studied [17]. The significance of traits of ASDs in children with attention deficit hyperactivity disorder (ADHD) has been studied in a clinical sample recruited through child psychiatry and pediatric outpatient clinics in the United Kingdom [5].…”
mentioning
confidence: 99%
“…Several experimental tasks have also been used to assess emotional processing, such as computer-presented pictures [35], printed cartoon pictures [14], a morphing task [13] and an emotional dotEmotion in Oppositionality and CU 17 17 probe [38] to cite some examples. Different reporters have mentioned behaviour problems (including mixing ODD and CD symptoms) and callous-unemotional traits, with a predominance of parents and children as reporters, while only a few studies have included teachers' ratings.…”
Section: Discussionmentioning
confidence: 99%
“…Children with low CU traits have been shown to respond more slowly to fearful eyes than to calm eyes [16] and they also display increased amygdala reactivity. Other studies have concluded that they are also less accurate in labelling fear [14] and they need more time to identify sadness, fear and happiness [13]. Conversely, there are also inconsistencies in the results on emotion recognition in children with conduct problems without CU traits.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation